Anda di halaman 1dari 3

ELEN3801

Homework 1 - Solution

1.1

Exercise 1

(a)
p

r = 32 + 4 2 = 5
4
= arctan
= 0.9273(rad)
3
(b)
p

72 + 5 2 =

74
5
= arctan = 0.6202(rad)
7
r=

(c)
p

r = 232 + 72 = 578
7
= arctan
= 2.8462(rad)
23

(d)
p

1002 + 462 = 12, 116


46
= arctan
+ = 2.7105(rad)
100
r=

1.2

Exercise 2

(a)
z=j
(b)

z = 5 cos(/3) + 5j sin(/3) = 5/2 j5 3/2


(c)

z = 4 cos(2/3) 4j sin(2/3) = 2 + j2 3
(d)
z = 6 cos(3 + /2) + 6j sin(3 + /2) = j6
(e)

z = 7 cos(4/3) + 7j sin(4/3) = 7/2 j7 3/2

1.3

Exercise 3
z1 = 7 5j = 8.6023ej0.6202
z2 = 3 + 4j = 5ej2.2143

(a)
z1 z2 = (8.6023 5)ej(2.21430.6202) = 43.0115ej1.5941 = 1 + 43j
(b)
z1 /z2 = (8.6023/5)ej(0.62022.2143) = 1.7205ej2.8345 =

41
13
j
= 1.64 0.52j
25
25

(c)
z2 /z1 =

1.4

1
13
1
41
ej2.8345 = 0.5812ej2.8345 = + j
= 0.5541 + 0.1757j
=
z1 /z2
1.7205
74
74

Exercise 4
f (x) = x3 4x2 + 8x = x(x2 4x + 8) = 0
(
)

4 16 32
Solutions in the complex plane = 0,
2

(a) {0}
(b) {0, 2 + 2j, 2 2j}
(c) The two non-real solutions are complex conjugates.

1.5

Exercise 5
f (t) =

4 6tj
with t real.
2 + tj

(a)
f (t) =

4 6tj 2 tj
8 4tj + 12tj 6t2
8 6t2
8t
=
=
+
j
2 + tj 2 tj
22 + t 2
4 + t2
4 + t2

(b)
|f (t)| =
=

1 q
1 q
2 )2 + (8t)2 =
(8

6t
(8 + 6t2 )2 + (8t)2
4 + t2
4 + t2
1 p
1 p 4
4 + 96t2 + 64t2 =
64
+
36t
36t + 160t2 + 64
4 + t2
4 + t2

To compute the angle, note that the real part of f (t) is always negative. Then, f (t) will
always be on the second or third quadrants.
8t
8t
= arctan
2
(8 + 6t )
8 + 6t2


f (t) = arctan

1.6

Exercise 6
C cos(wt + ) = C cos() cos(wt) C sin() sin(wt)

(a)
f (t) = 6 cos(wt)

5 sin(wt)

C =
36 + 5 = 41 = 6.4031
6 = C cos()
5 = C sin()
= arctan( 65 ) = 0.3567(rad)
(b)
f (t) = 18 cos(wt) + 2 sin(wt)

18 = C cos()
182 + 4 = 328 = 18.1108
C =

2
2 = C sin()
= arctan( 18
) = 3.0309(rad)

1.7

Exercise 7

We need to prove that


cos( + ) = cos cos sin sin
sin( + ) = sin cos + cos sin
Assume that we have two complex numbers z1 and z2 , both with unit magnitude
z1 = ej = cos + j sin
z2 = ej = cos + j sin
We can multiply them in two different ways:
z1 z2 = e(+)j = cos( + ) + j sin( + )
z1 z2 = (cos + j sin )(cos + j sin )
Then
cos( + ) + j sin( + ) = (cos + j sin )(cos + j sin )
= cos cos + cos sin j + sin cos j sin sin
= (cos cos sin sin ) + (cos sin + sin cos )j
Which implies that
cos( + ) = cos cos sin sin
sin( + ) = cos sin + sin cos